Varietal Performances and Foliar Application of Nutrients on Yield and Economics of Utera Rapeseed-Mustard in Rice-Fallow of Alluvial Soils - Saha, Somnath; Barik, Arun Kumar; Kumar, Basant (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during winter seasons (November to February) of 2020–21 and 2021–22 to evaluate performances of different rapeseed-mustard varieties under foliar spray of nutrients on growth, yield components, yield and economics of utera (relay) rapeseed-mustard grown in rice–fallow. The experiment was laid out in a split plot design keeping rapeseed-mustard varieties, viz., Anushka, Binoy and PM-28 in main plots and eight different foliar spray of nutrients in sub-plots. Variety PM 28 registered significantly higher growth attributes, yield components, seed yield (1198.5 kg ha-1), stover yield (3300.4 kg ha-1) and biological yield (4498.8 kg ha-1) and also achieved significantly higher return per rupee invested (`Rs. 2.05) over other two varieties. Foliar spray of N:P:K (19:19:19) @2% twice at 30 DAS and 45 DAS+ZnSO4 @ 0.05% at 40 DAS+Boron (20%) @ 0.1% at 50 DAS was found significantly superior to all other foliar sprays with respect to yield components and seed yield (1233.2 kg ha-1), stover yield (3109.9 kg ha-1) and biological yield (4343.2 kg ha-1) irrespective of the varieties and also gave significantly higher return per rupee invested (Rs. 1`.93) over other foliar application. The study revealed that, cultivation of rapeseed-mustard along with foliar application of nutrients in rice fallow of alluvial soils of West Bengal was a better option to enhance growth, productivity and economics of utera rapeseed-mustard.